(untitled) (Contemporary Journal of Social Science Review, 2025)
Amid volatile emerging-economy conditions, this study investigates how process innovation drives non-financial venture performance in Pakistani SMEs and whether market knowledge and government support strengthen this relationship. A cross-sectional survey of 395 SME owners/managers across ten Punjab divisions was analysed via PLS-SEM (SmartPLS 4.0 & WarpPLS 8.0). Process innovation significantly improves venture performance (β = .294, p < .001). Entrepreneurial education (β = .275) and digital readiness (β = .348) influence performance indirectly via process innovation (partial mediation). Government support positively moderates the innovation–performance link (β = .428, p = .012); market knowledge does not (β = .502, p = .150). Policymakers should simplify innovation-grant access; SME owners should leverage targeted training and phased digital adoption. Integrates Resource-Based and Knowledge-Based Views to explain non-financial SME performance in an emerging-market context.